PENGARUH LEVERAGE, PROFITABILITY, DAN CAPITAL INTENSITY RATIO TERHADAP EFFECTIVE TAX RATE (ETR) (STUDY KASUS PADA PERUSAHAAN KONTRUKSI DAN REAL ESTATE YANG TERDAFTAR PADA BEI TAHUN 2014-2018) - Pristanti, Apriliya; Harimurti, Fadjar; Suharno, Suharno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2020)
Effective tax rate (ETR) is basically a presentation of the amount of tax rates borne by the company. This study aims to examine and analyze the effect of Leverage, Profitability, and Capital Intensity Ratio on the Effective Tax Rate. The population in this study is the Construction and Real Estate Companies in the Indonesia Stock Exchange in 2014-2018. The population of this research is 48 Construction and Real Estate companies in the Indonesia Stock Exchange in 2014-2018. Sampling using a purposive sampling technique, selected companies as many as 20 companies. The data analysis technique used is multiple linear regression. The results of this study indicate that leverage has a positive and significant effect on the Effective Tax Rate. Profitability has a negative and significant effect on Effective Tax Rate. Capital Intensity Ratio has no effect on the Effective Tax Rate. The benefit of this research is that it can broaden horizons and at the same time gain knowledge about leverage, profitability, capital intensity ratio to the effective tax rate.